具有优异倍率性能复合电极材料的制备方法 (2018)
本发明公开了具有优异倍率性能复合电极材料的制备方法，以苯胺单体和磺化石墨烯充分混合均匀，原位聚合合成聚苯胺－磺化石墨烯复合材料，再与聚偏氟乙烯、乙炔黑进行研磨均匀，采用N-甲基吡咯烷酮为溶剂，将浆料涂覆在集流体不锈钢片上干燥，即可得到复合电极材料。本发明的技术方案制得的复合电极材料，具有倍率性能优异，循环稳定性好，比电容高等优点，适合用于超级电容器电极材料。 The invention discloses a composite electrode material having excellent rate performance and a preparation method thereof. The preparation method comprises the following steps: fully mixing an aniline monomer with sulfonated graphene uniformly; performing in-situ polymerization to synthesize a polyaniline-sulfonated graphene composite material; grinding uniformly with polyvinylidene fluoride and acetylene black; preparing N-methyl pyrrolidone as a solvent; coating slurry on a current collector stainless steel sheet for drying to obtain the composite electrode material. The composite electrode material prepared according to the technical scheme has the advantages of excellent rate performance, high circulation stability, high specific capacitance and the like, and is suitable for a super capacitor electrode material.